Understanding Homeownership Rates: the Impact of Co-residence Patterns - Edyta Marcinkiewicz (Critical Housing Analysis)
The socio-demographic context, which includes the co-residence patterns associated with the decisions of young adults on whether to live in the parental household or enter homeownership or renting, is directly reflected in homeownership rates at the aggregate level as a consequence of these decisions. However, the way in which tenure statistics are reported also matters in this respect. This applies specifically to household-level statistics, which are most often used to characterise housing systems. It is therefore possible to ask whether countries with high homeownership rates and, simultaneously, high shares of adult children living with their parents are truly high-homeownership societies. This study identifies the countries for which the reported tenure statistics are more influenced by demographic conditions as compared to other countries. These are the Mediterranean countries and the Central and Eastern European countries (with some exceptions).